Environmental conservation in biology learning: An effort to increase students' awareness of environmental issues - Nofamataro Zebua; Yan Piter Basman Ziraluo; Ester Novi Kurnia Zebua (International Journal of Advances in Educational Research, 2025)
Environmental degradation in Indonesia, including deforestation, plastic pollution, and biodiversity loss, poses serious threats to ecosystems and human well-being. Integrating environmental conservation into biology learning is crucial to fostering students' awareness and responsible behavior toward environmental issues. This study employs a qualitative approach through literature review and curriculum analysis to examine the integration of conservation themes in biology education. Findings suggest that project-based and contextual learning effectively enhance students' understanding and engagement with real environmental challenges. The use of digital tools further supports interactive learning experiences, promoting critical thinking and problem-solving skills. However, challenges such as limited resources and insufficient teacher training hinder effective implementation. Strengthening teacher capacity, improving curriculum design, and fostering collaboration among schools, government, and environmental organizations are essential to enhancing environmental education. This study underscores the potential of biology learning as a transformative tool in shaping a generation that is not only academically proficient but also environmentally conscious and proactive in sustainability efforts.